Impact of Different Concentrations of Aluminum Chloride on Callus Induction and Organogenesis in Date Palm (Phoenix dactylifera L.) cv. "Barhi" - Zainab Tariq Safi Al Ali; Majid Abdulhameed Ibrahim; Khaun Ali Muhsen (University of Thi-Qar Journal of agricultural research, 2024)
The present study was conducted in the Plant Tissue Culture Laboratory, Date Palm Research Center, University of Basrah, Basrah, Iraq for the years 2023 and 2024. The investigation aims to test the effect of adding different concentrations of aluminum chloride (0, 15, 30, and 45mg L-1) to the MS medium prepared to induce callus and indirect shoot regeneration of date palm (Phoenix dactylifera L. cv. Barhi) grown using an in vitro culture technique. The results showed that the aluminum chloride treatment at a concentration of 45mg L-1 significantly outperformed the 15 mg L-1 treatment of aluminum chloride and the control treatment in response to callus induction (%), fresh and dry weight (mg). The control treatment recorded the lowest values in response to callus induction and fresh and dry callus weight. The results indicate that the aluminum chloride treatment at a concentration of 45mg L-1 significantly outperformed the 15mg L-1 treatment of aluminum chloride and the control treatment in response to shoot regeneration, number of shoots per culture, shoot length, and number of leaves per shoot. The control treatment recorded the lowest values in these characteristics.